Integrated analysis of miRNAome transcriptome and degradome reveals miRNA-target modules governing floral florescence development and senescence across early- and late-flowering genotypes in tree peony - Guo, Lili; Li, Yuying; Zhang, Chenjie; Wang, Zhanying; Carlson, John E.; Yin, Weinlun; Zhang, Xiuxin; Hou, Xiaogai (Frontiers in Plant Science, 2022)
As a candidate national flower of China, tree peony has extremely high ornamental, medicinal and oil value. However, the short florescence and rarity of early-flowering and late-flowering varieties restrict further improvement of the economic value of tree peony. Specific miRNAs and their target genes engaged in tree peony floral florescence, development and senescence remain unknown. This report presents the integrated analysis of the miRNAome, transcriptome and degradome of tree peony petals collected from blooming, initial flowering, full blooming and decay stages in early-flowering variety Paeonia ostii ‘Fengdan’, an early-flowering mutant line of Paeonia ostii ‘Fengdan’ and late-flowering variety Paeonia suffruticosa ‘Lianhe’. Transcriptome analysis revealed a transcript (‘psu.G.00014095’) which was annotated as a xyloglucan endotransglycosylase/hydrolase precursor XTH-25 and found to be differentially expressed across flower developmental stages in Paeonia ostii ‘Fengdan’ and Paeonia suffruticosa ‘Lianhe’. The miRNA-mRNA modules were presented significant enrichment in various pathways such as plant hormone signal transduction, indole alkaloid biosynthesis, arachidonic acid metabolism, folate biosynthesis, fatty acid elongation, and the MAPK signaling pathway. Multiple miRNA-mRNA-TF modules demonstrated the potential functions of MYB-related, bHLH, Trihelix, NAC, GRAS and HD-ZIP TF families in floral florescence, development, and senescence of tree peony. Comparative spatio-temporal expression investigation of eight floral-favored miRNA-target modules suggested that transcript ‘psu.T.00024044’ and microRNA mtr-miR166g-5p are involved in the floral florescence, development and senescence associated agronomic traits of tree peony. The results might accelerate the understanding of the potential regulation mechanism in regards to floral florescence, development and abscission, and supply guidance for tree peony breeding of varieties with later and longer florescence characteristics.